(untitled) - Nguyen, Duc Cuong; Nicolaisen, Mette Haubjerg
Springer Science+Business Media, LLC 2011
Keywords: Nông - Lâm - Nghiệp; Rice; Rhizoctonia solani AG1-IA; Biological Control; Sheath blight; Hyphae-Colonizing Burkholderia sp.; Viet Nam